The Role of The Villain as A Determinant of The Existence of The Main Character - Anindya Putri Pradiptha (Universitas Dian Nuswantoro, 2018)
Abstract. Comic is one of the popular literary works that combining pictures and languages. It can be a work if it consist of story that using language as the medium. The aims of this study is to explain the formula of the comic by using theories of comic, escapism, and the narrationâ€™s structure of an adventure comics, The Life and Times Of Scrooge McDuck created by Don Rosa. To get relevant data, this study is employ one method, namely; library study. In this paper, the writer used theories of comic by Scott McCloud, escapism by Cawelty, and the narrationâ€™s structure of Vladimir Propp. The result indicates that in this comic, there is the reality of the idea that the existence of the main character is manifested by the presence of the villains. Comic is a complete books that can teaching the reader which is not only understand the stories, but also the world view inside, it is the goodÂ ideology of the existence from the bad side.Keywords: comic, escapism, narration, existence, and the villains.Abstrak. Komik adalah salah satu karya sastra populer yang menggabungkan gambar dan bahasa. Hal ini dapat bekerja jika itu terdiri dari cerita yang menggunakan bahasa sebagai media. Tujuan dari penelitian ini adalah untuk menjelaskan formula komik dengan menggunakan teori komik, melepaskan diri, dan narasi struktur komik petualangan, hidup dan Gober Bebek dibuat oleh Don Rosa. Untuk mendapatkan data yang relevan, studi ini menggunakan satu teknik, yaitu; studi perpustakaan. Dalam tulisan ini, penulis menggunakan teori Komik oleh Scott McCloud, eskapisme oleh Cawelty, dan struktur narasi Vladimir Propp. Hasilnya menunjukkan bahwa di komik ini, ada realitas gagasan bahwa keberadaan karakter utama diwujudkan oleh kehadiran penjahat. Komik sebuah bacaan yang berisi, mendidik, dan berbobot, karena melalui komik pembaca tidak hanya memahami ceritanya saja, tetapi realitas ide di baliknya, yakni ideologi baik dari keberadaan si pelaku kejahatan.Kata kunci: komik, eskapisme, narasi, keberadaan, dan para penjahat.